2017
DOI: 10.1111/cei.12981
|View full text |Cite
|
Sign up to set email alerts
|

Operational tolerance in kidney transplantation and associated biomarkers

Abstract: SummaryIn the 1960s, our predecessors won a historical battle against acute rejection and ensured that transplantation became a common life-saving treatment. In parallel with this success, or perhaps because of it, we lost the battle for long-lived transplants, being overwhelmed with chronic immune insults and the toxicities of immunosuppression. It is likely that current powerful treatments block acute rejection, but at the same time condemn the few circulating donor cells that would have been able to elicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 146 publications
1
24
0
2
Order By: Relevance
“…144 Kidneys, unlike the liver, are unable to regenerate after insult and even mild episodes of rejection can cause permanent damage that increases the risk of eventual graft failure. 144 Kidneys, unlike the liver, are unable to regenerate after insult and even mild episodes of rejection can cause permanent damage that increases the risk of eventual graft failure.…”
Section: Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…144 Kidneys, unlike the liver, are unable to regenerate after insult and even mild episodes of rejection can cause permanent damage that increases the risk of eventual graft failure. 144 Kidneys, unlike the liver, are unable to regenerate after insult and even mild episodes of rejection can cause permanent damage that increases the risk of eventual graft failure.…”
Section: Kidneymentioning
confidence: 99%
“…In contrast to liver transplantation, operational tolerance after kidney transplantation is rare. 144 Kidneys, unlike the liver, are unable to regenerate after insult and even mild episodes of rejection can cause permanent damage that increases the risk of eventual graft failure. Past studies have shown that withdrawal or slight alteration of immunosuppression after kidney transplantation is associated with rejection.…”
Section: Kidneymentioning
confidence: 99%
“…[126][127][128][129] Some of these "tolerant" recipients have antibodies in the circulation specific for antigens in the graft. What is important for the present is that these mechanisms limit the im- to have spontaneously developed tolerance to their grafts.…”
Section: Accommodationmentioning
confidence: 99%
“…[126][127][128][129][130] One might expect that tolerance to a transplant would be readily identified. Yet, investigation of autoimmune-and alloimmunemediated disease usually focuses on changes in the immune response rather than susceptibility to injury.…”
Section: Accommodationmentioning
confidence: 99%
See 1 more Smart Citation